Ultrasound Guided Catheterization of Internal Jugular Vein Technique Versus Standard Landmark Technique - Shizan Hamid Feroz,Syed Hamid Ali Shah,Faisal Wahid (Journal of Rawalpindi Medical College, 2014)
Background: To compare, average access time, number of attempts and the complications resulting from cannulation of internal jugular vein by standard landmark technique with real-time ultrasound guided technique. Methods : In this comparative study, patients(n=200) undergoing different types of major surgical procedures, were divided in two groups. Anaesthetists and other staff were blinded to the randomization schedule and block size. After successfully securing the endotracheal tube, patients were placed in supine position with 15 degree head down.CV lines were first attempted on right side of neck and patients face was turned to left. On real time ultrasound unit carotid artery was selected and linear- arry ultrasound probe was attached to it and gel was applied to it and wrapped in a sterile plastic sheath. Transducer was placed parallel and superior to right clavicle over the groove between sternal and clavicular heads of sternocleidomastoid. This readily visualized internal and external jugular vein and carotid artery. Real time two dimensional view was used to identify Internal jugular vein and after checking its compressibility , an 18G, 10cm needle was advanced through skin under ultrasound guidance. After successful aspiration of blood a guide wire was placed through needle and needle was removed and after dilating the tract with dilator a CV line was placed over guide wire. In land mark technique patients were prepared in the similar manner as for ultrasound guided technique. A 10cm 18-gauge needle attached with 10 ml syringe was introduced in the direction of respective nipple (right or left side) at the apex of triangle made by sternal and clavicular heads of sternocleidomastoid muscle. Return of venous blood in to syringe on aspiration was taken as confirmation of entry in to vein but color of blood and pressure of flow back was used as indicator whether needle has accidentally punctured the carotid artery or not. Results: Both the groups were similar with respect to age, gender, weight , site of cannulation, and for presence of risk factors for difficult cannulation. Hematoma was observed in only one patient in ultrasound group as compared to nine patients in landmark group. Haemothorax and pneumothorax were not observed in any patient in ultrasound group. In land mark group 2% had haemothorax and 3% had pneumothorax.. Carotid puncture was noted in 7% in landmark group , while in ultrasound group carotid puncture was not observed(p less than 0.050).Average access time was significantly lower in ultrasound group than in landmark group. Procedure success rate was 100% in ultrasound group and 95% in landmark group. Conclusion: Ultrasound guided technique, as compared with landmark technique, is effective in reducing the complications associated with central venous cannulation.